Patterns of Alcohol Consumption as a Social Group Indicator in Modern Russian Cities - Roshchina, Yana; Martynenko, Petr (Journal of Economic Sociology, 2014)
This article analyzes the correlation between alcohol consumption patterns in Russian cities and the characteristics of consumers, including their social status. The empirical dataset used in this study was generated from the Russian Target Group Index for 2000–2010 and produced by Synovate Comcon. The methods used in the study include correlation analyses, cluster analyses and correspondence analyses. The results of the study confirm that differences in alcohol consumption patterns are important characteristics of social groups — stratified by gender, age, education and income — in Russia. Beer, vodka and other spirits are typically consumed by men, whereas wine, champagne and liquors are typical consumed by women. The different social classes also have different chosen beverages: the highest social classes prefer wine, champagne, cognac, whisky and exotic beverages such as rum and tequila. The volume of consumed alcohol is not an indicator of social class. Beer and vodka — beverages consumed by all social groups — are mostly consumed by the poorer and less educated. This study also identified the following consumer clusters: “light drink lovers” (beer-oriented consumption), the “masculine consumer” (consumption of beer and vodka), the “feminine consumer” (wine- and champagne-oriented consumption), and the “eclectic type” (multi-oriented consumption). These clusters have different social and demographic characteristics. In modern Russia, patterns of alcohol consumption and the social class of the consumer tend to be highly correlated. Variegated consumption patterns associated with the postmodern lifestyle were detected in fewer than 5% consumers of alcohol; these consumers tended to be educated, well-off, young and employed in executive positions.